Role of the Double Muscle Gastrocnemius-Soleus Flap in Soft Tissue Defect Reconstruction of the Leg in Children: Case Series - Kalluraya, Suryakanth; Kammar, Shershah Fakruddin; Hosangadi, Adiveppa; Kumar, Akash (Scripta Medica, 2023)
The reconstructive surgeon faces a problem when dealing with larger soft tissue lesions over the knee and the proximal two thirds of the tibia, two crucial sites of the lower limb. Large free flaps or pedicled local flaps are two solutions of the problem. The soleus or gastrocnemius flaps by itself are insufficient. Without using free flaps, combined gastrocnemius-soleus flaps can be employed effectively. Indicators for this kind of flap are still quite uncommon in children. In two clinical cases, authors will share their expertise and talk about the use of this kind of flap in the treatment of soft tissue abnormalities in children. Two cases were outlined: the use and outcome of the combination pedicled gastrocnemius-hemisoleus double muscle flap to repair significant defects around the knee and leg in children.